STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN ALAT KESEHATAN DI UD. PUTRA PRATAMA 14 SURABAYA - Suzan Fhelda Febrina; Achmad Daengs GS (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
To win competition in business world, all businessman must have selling method effective efficiently in order to get right target and low east, toreach the target, the company should have same index parameter. To measurequality of service that be given to customer, many company try to implementservice excellence, but fail, meanwhile the company is given out cost, time,power no so a little to do some training for his employees, what problem ?,actually, just giving training is not one solution because, familiarization, andmanner to save customer is not so enough will be paradigm and skill for frontline to save the customer, but seriously, high commitment at each oforganization especially top management service excellence must beimplemented in structural oriented at each of company.Key Word : Desired outcome , customer expectation, process capability, serviceexcellence